2012 IEEE International Symposium on Multimedia 2012
DOI: 10.1109/ism.2012.54
|View full text |Cite
|
Sign up to set email alerts
|

Level-Based Peer-to-Peer Live Streaming with Rateless Codes

Abstract: Abstract-We propose a peer-to-peer system for streaming user-generated live video. Peers are arranged in levels so that video is delivered at about the same time to all peers in the same level, and peers in a higher level watch the video before those in a lower level. We encode the video bitstream with rateless codes and use trees to transmit the encoded symbols. Trees are constructed to minimize the transmission rate for the source while maximizing the number of served peers and guaranteeing on-time delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A demo of the proposed system was presented at the 2012 IEEE International Conference on Peer-to-Peer Computing [16]. A simplified version of the system that targets static scenarios in which all peers join before the start of the video session and remain subscribed until the end of the session was described in a conference paper [17]. Simulations showed that the system can sustain high performance as long as the number of peers that leave the system is moderate.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A demo of the proposed system was presented at the 2012 IEEE International Conference on Peer-to-Peer Computing [16]. A simplified version of the system that targets static scenarios in which all peers join before the start of the video session and remain subscribed until the end of the session was described in a conference paper [17]. Simulations showed that the system can sustain high performance as long as the number of peers that leave the system is moderate.…”
Section: Related Workmentioning
confidence: 99%
“…-Replacing leaves in other trees after inserting them into the peer's trees: If the peer still has not been spanned in K trees, we use Algorithm 3 to insert leaves with maximum spare capacity into the peer's trees with smallest size. These leaves are taken from trees with maximum size that do not contain the peer (lines [13][14][15][16][17][18][19][20]. The leaves are then replaced by the peer (line 21).…”
Section: Forest Construction -Insertionmentioning
confidence: 99%